Glyphosate-induced hormesis: impact on seedling growth and reproductive potential of common sowthistle (Sonchus oleraceus). Issue 6 (12th November 2020) - Mobli, Ahmadreza; Matloob, Amar; Chauhan, Bhagirath Singh
Abstract: In Australia, glyphosate is widely used in glyphosate-tolerant crops and fallows to control weeds such as common sowthistle ( Sonchus oleraceus L.). It has been hypothesized that glyphosate at sublethal doses, as a consequence of herbicide drift, may have a stimulatory effect on S. oleraceus growth. In 2017, pot trials were conducted to evaluate the effect of low doses of glyphosate on growth and seed production of this weed at the Weed Science Screenhouse Facility at the University of Queensland, Australia. At the 4- to 5-leaf stage (3-wk-old rosette), plants were treated with low doses of glyphosate (0 [control], 5, 10, 20, 40, 80, and 800 g ae ha −1 ), and their responses were recorded until plant maturity. The study was repeated after completion of the first experimental run. An additional glyphosate dose (2.5 g ha −1 ) was added in the second run. The low doses of glyphosate (<40 g ha −1 ) caused a significant increase in S. oleraceus plant height and number of leaves compared with the no-glyphosate treatment. The highest stimulatory effect was observed at 5 g ha −1 . At 5 g ha −1 glyphosate, S. oleraceus seed production increased by 154% and 101% in the first and second experimental runs, respectively, compared with the no-glyphosate treatment. The results of this study suggest that the sublethal doses of glyphosate produced hormetic effects on growth and seed production of S. oleraceus that changed the dynamics of weed–crop competition.